The use of an external skeletal traction device for distal fractures in the dog - Risselada, M.; Verleyen, P.; van Bree, H.; Verhoeven, G. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
Metacarpal and metatarsal fractures in 11 patients were treated ‘closed’ with a specially designed External Skeletal Fixation (ESF) frame with a walking bar and traction applied to the digits. Mediolateral angulation had improved postoperatively in 10 of the 11 patients. Craniocaudal angulation had improved in eight patients and could not be evaluated in three due to ESF frame superimposition. At follow-up, eight patients had a good clinical function, whereas three patients were still slightly lame. Only minor ESF-related complications were seen (pin loosening, pin tract infection, cerclage wire breakage and bending of the frame), which resolved without intervention after frame removal.
Keywords: Fractures; external skeletal fixation; dogs